Catch me if you can: antipredatory behaviour of chamois to the wolf. Issue 6 (2nd November 2017) - Baruzzi, Carolina; Lovari, Sandro; Fattorini, Niccolò
Abstract : Antipredator behaviour is a multifactorial process – e.g. landscape features, escape tactics of prey, probability of encountering predators, predator type, age, sex and physical state of prey. Ungulates show a wide range of antipredator ploys. As reactions of mountain ungulates to their predators are still poorly understood, we hereby report on two interactions between Apennine chamois Rupicapra pyrenaica ornata and wolves Canis lupus in a protected area in the Central Apennines, Italy. Male and female chamois showed different reactions to the presence of the wolf. While females and juveniles fled to steeper, higher terrain upon the arrival of the wolf, males showed alternative antipredator tactics. In one case, the only male chamois present did not flee, but kept watching the movements of the wolf from a slab of rock at the foot of a steep scree, i.e. close to a potential escape terrain. In the other case, the two males present rushed to hide in the forest. Females formed a barrier between their kids and the wolf. Vigilance increased greatly, although chamois resumed their normal feeding activities within ca 10 min of the wolf visits. Fleeing of herd members in different directions may have helped to confuse the predator. In both cases, the antipredator behaviour of chamois proved successful to prevent predation.